2013
DOI: 10.4161/cc.23177
|View full text |Cite
|
Sign up to set email alerts
|

Separation of intra-S checkpoint protein contributions to DNA replication fork protection and genomic stability in normal human fibroblasts

Abstract: Separation of intra-S checkpoint protein contributions to DNA replication fork protection and genomic stability in normal human fibroblasts, Cell Cycle, 12:2, 332-345,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 70 publications
(91 reference statements)
3
19
0
Order By: Relevance
“…3D). Because claspin regulates DNA replication in normal cells, we performed cell cycle analysis on the ATC cells after YM155 treatment (3–8 nM vs. vehicle) (17, 18). YM155 treatment increased the number of cells in S phase (by 14–34%) and decreased the number of cells in G 0 G 1 in the ATC cell lines tested (8505C, C643, and SW1736) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3D). Because claspin regulates DNA replication in normal cells, we performed cell cycle analysis on the ATC cells after YM155 treatment (3–8 nM vs. vehicle) (17, 18). YM155 treatment increased the number of cells in S phase (by 14–34%) and decreased the number of cells in G 0 G 1 in the ATC cell lines tested (8505C, C643, and SW1736) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The clonogenic survival assays were performed as previously described [72]. Briefly, NHF1-hTERT cells electroporated with siRNAs were seeded at a density that would result in ~150 colonies per 10 cm dish for the NTC siRNA control.…”
Section: Methodsmentioning
confidence: 99%
“…3 Abrogation of the ATR/ CHK1 pathway has clearly been shown to inhibit the intra-S checkpoint to UV 6,8 and to lead to an increase in chromosomal instability. 18 Despite these observations, it is less clear whether abrogation of the ATR/CHK1-dependent S-phase checkpoint influences mutagenesis. To address this question, we employed siRNA-mediated depletion of ATR or CHK1, or pharmacological inhibition of CHK1 kinase function to inactivate the intra-S checkpoint and measured mutation frequency at the HPRT locus in UV-irradiated human fibroblasts.…”
Section: Introductionmentioning
confidence: 96%
“…If ATR or CHK1 were important for efficient bypass synthesis (in addition to their known checkpoint functions), it stands to reason that the depletion of these enzymes might inhibit TLS and reduce mutation frequency. It has been suggested that ATR, CHK1, and other components of the replication fork protection complex not only participate in the activation of the intra-S checkpoint, but also possess separate functions for preservation of intrinsic chromosomal stability, 18 particularly at common fragile sites. 48,49 Common fragile sites tend to be replicated late in S phase; the formation of secondary structures within the fragile sites is thought to slow progression of replication forks.…”
Section: 32mentioning
confidence: 99%